A novel conservative chaos driven dynamic DNA coding for image encryption - Patidar, Vinod; Kaur, Gurpreet (Frontiers in Applied Mathematics and Statistics, 2023)
Recently, many image encryption algorithms based on hybrid DNA and chaos have been developed. Most of these algorithms utilize chaotic systems with dissipative dynamics and exhibiting periodic windows and patterns in bifurcation diagrams along with co-existing attractors in the neighbourhoods of parameter space. Therefore, such algorithms generate several weak keys, thereby making them prone to various chaos- specific attacks. In this paper, we propose a novel conservative chaotic standard map-driven dynamic DNA coding (encoding, addition, subtraction and decoding) for image encryption. It is the first hybrid DNA and conservative chaos-based image encryption algorithm having effectively infinite key space. The proposed image encryption algorithm is a dynamic DNA coding algorithm i.e., for the encryption of each pixel different rules for encoding, addition/subtraction, decoding etc. are randomly selected based on the pseudorandom sequences generated with the help of the conservative chaotic standard map. We propose a novel way to generate pseudo-random sequences through the conservative chaotic standard map and also test them rigorously through the most stringent test suite of pseudo-randomness, the NIST test suite, before using them in the proposed image encryption algorithm. Our image encryption algorithm incorporates unique feed-forward and feedback mechanisms to generate and modify the dynamic one-time pixels that are further used for the encryption of each pixel of the plain image, therefore, bringing in the desired sensitivity on plaintext as well as ciphertext. All the controlling pseudorandom sequences used in the algorithm are generated for a different value of the parameter (part of the secret key) with inter-dependency through the iterates of the chaotic map (in the generation process) and therefore possess extreme key sensitivity too. The performance and security analysis has been executed extensively through histogram analysis, correlation analysis, information entropy analysis, DNA sequence-based analysis, perceptual quality analysis, key sensitivity analysis, plaintext sensitivity analysis, classical attack analysis, etc., The results are promising and prove the robustness of the algorithm against various common cryptanalytic attacks.